Phosphoglycerate mutase 1 in cancer: A promising target for diagnosis and therapy. Issue 10 (6th June 2019) - Sharif, Farzana; Rasul, Azhar; Ashraf, Asma; Hussain, Ghulam; Younis, Tahira; Sarfraz, Iqra; Chaudhry, Muhammad Asrar; Bukhari, Shazia A.; Ji, Xin Y.; Selamoglu, Zeliha; Ali, Muhammad
Abstract: Altered enzymatic machineries are a substantial biochemical characteristic of tumor cell metabolism that switch metabolic profile from oxidative phosphorylation to amplified glycolysis as well as increased lactate production under hypoxia conditions. Reprogrammed metabolic profile is an emerging hallmark of cancer. Overexpression of several glycolytic enzymes and glucose transporters has been reported in 24 different types of cancers that represent approximately 70% of all the cancer cases around the globe. Thus, targeting glycolytic enzymes could serve as tempting avenue for drug design against cancer. Phosphoglycerate mutase 1 (PGAM1) is an important glycolytic enzyme that catalyzes the conversion of 3‐phosphoglycerate to 2‐phosphoglycerate. Recent investigations have revealed the overexpression of PGAM1 in several human cancers that is linked with tumor growth, survival, and invasion. The aim of this review is to update scientific research network with cancer‐specific role of PGAM1 to elucidate its capability as bonafide therapeutic target for cancer therapy. Moreover, we have also summarized the reported genetic and pharmacological inhibitors of PGAM1. This study suggests that further investigations on PGAM1 should focus on the exploration of molecular mechanisms of PGAM1 overexpression in development of cancer, assessment of biosafety profiles of known inhibitors of PGAM1, and utilization of PGAM1 inhibitors in combinatorial therapies. These future studies will surely support the unbiased strategies for the development of novel PGAM1 inhibitors for cancer therapies.